Reduction in cardiovascular disease events in patients with type 2 diabetes mellitus treated with a sodium–glucose cotransporter 2 inhibitor versus a dipeptidyl peptidase‐4 inhibitor: A real‐world retrospective administrative database analysis in Japan. Issue 7 (9th April 2022) - Kashiwagi, Atsunori; Shoji, Shingo; Onozawa, Satoshi; Kosakai, Yoshinori; Waratani, Miina; Ito, Yuichiro
Abstract: Aims/Introduction: To evaluate the benefit of sodium–glucose cotransporter 2 inhibitors (SGLT2i) versus dipeptidyl peptidase‐4 inhibitors (DPP4i) in reducing cardiovascular disease (CVD) events in patients with type 2 diabetes mellitus with and without a CVD history. Materials and Methods: This retrospective cohort study used Japanese hospital administrative data from the Medical Data Vision database (January 2015 to April 2020). Patients with type 2 diabetes mellitus ( n = 625, 739) who were new users of an SGLT2i ( n = 57, 070; 9.1%) or DPP4i ( n = 568, 669; 90.9%) were included. Outcomes included hospitalization for heart failure (hHF), all‐cause death (ACD) and the composite of hHF or ACD. Hazard ratios (HR) were calculated using the inverse probability weighting Cox proportional hazards model to compare CVD event risks between treatment groups. Results: Compared with DPP4i, SGLT2i was associated with a significant reduction in hHF risk among patients without a CVD history (HR 0.507, 95% confidence interval 0.283–0.907), but not in the full cohort or those with a CVD history. SGLT2i was associated with a significant risk reduction of ACD (HR 0.592, 95% confidence interval 0.481–0.729) and the composite of hHF or ACD (HR 0.712, 95% confidence interval 0.613–0.826), compared with DPP4i in the full cohort; similar results were observed among patients with and without a CVD history. Conclusions: In this real‐world study, SGLT2i versus DPP4i was associated with a significant reduction in hHF, ACD and hHF or ACD events in patients with type 2 diabetes mellitus without a CVD history. Abstract : Patients with type 2 diabetes mellitus have increased risk of developing cardiovascular events, and death. The present study using a Japanese administrative database has demonstrated that the use of sodium–glucose cotransporter 2 inhibitors is associated with a significant reduction in the risk of hospitalization for heart failure, all‐cause death, and the composite of hospitalization for heart failure or all‐cause death, compared with dipeptidyl peptidase‐4 inhibitors in patients with type 2 diabetes mellitus, particularly in those without a history of cardiovascular disease.